Hemoglobin is a key determinant of quality of life before and during azacitidine-based therapy for myelodysplasia and low blast count acute myeloid leukemia. Issue 3 (23rd February 2022) - McQuilten, Zoe K.; Busija, Ljoudmila; Seymour, John F.; Stanworth, Simon; Wood, Erica M.; Kenealy, Melita; Weinkove, Robert; ,
Abstract: Myelodysplastic syndromes (MDS) have a major impact on quality of life (QoL). We performed a post hoc analysis of two multicenter trials of azacitidine-based disease-modifying therapy for patients with MDS and low blast count acute myeloid leukemia (AML), to identify factors associated with QoL. 231 patients were included (median age 70 years). At baseline, higher initial hemoglobin, but not neutrophil or platelet count, was associated with better global QoL and physical function ( p  < 0.001 and p  = 0.001, respectively). During therapy, increase in hemoglobin was associated with improvement in QoL and physical function ( p  = 0.005 and p  < 0.001, respectively). Lower initial hemoglobin was associated with higher dyspnea and fatigue scores ( p  < 0.001 and p  = 0.001, respectively), and hemoglobin response was associated with improvement in dyspnea and fatigue ( p  < 0.001 for each). In patients with MDS and low blast count AML, hemoglobin level was strongly correlated with global QoL, physical functioning, dyspnea and fatigue, both before and during azacitidine-based therapy.